Immunosuppressant indulges EBV reactivation and related lymphoproliferative disease by inhibiting Vδ2+ T cells activities after hematopoietic transplantation for blood malignancies - Ning Wu; Jiangying Liu; Haitao Gao; Lan-Ping Xu; Xiao-Dong Mo; Ruoyang Liu; Shuang Liang; Ming Wang; Zhidong Wang; Ying-Jun Chang; Xiao-Hui Zhang; Xiao-Jun Huang (Journal for ImmunoTherapy of Cancer, 2020)
Background Following the extensive use of immunosuppressive drugs in the clinic, immunosuppression-associated side effects have received increasing attention. Epstein-Barr virus (EBV) reactivation and related lymphoproliferative diseases (LPD) are the lethal complications observed after allogeneic hematopoietic cell transplantation (alloHCT). While studies generally suggest an association between immunosuppressants and EBV reactivation, the effects of specific immunosuppressive drugs and which T-cell subsets mediate these correlations are unclear. Vδ2+ T cells are correlated with EBV reactivation after alloHCT. Researchers have not determined whether Vδ2+ T-cell activities are affected by immunosuppressants and thereby facilitate EBV reactivation and related LPD.Methods A clinical cohort study of 170 patients with hematopoietic malignancies who received haploidentical hematopoietic cell transplantation (haploHCT) was performed to investigate whether the early cessation of mycophenolate mofetil (MMF) decreases EBV reactivation and related LPD and to determine whether this change is associated with the recovery of Vδ2 + T cells after transplantation. The effects of MMF on the expansion and anti-EBV capacity of Vδ2+ T cells were detected in vitro and in an immunodeficient mouse model.Results A reduction in the course of MMF significantly improved the recovery of Vδ2+ T cells from 30 to 90 days after haploHCT (p=0.002, p=0.042 and p=0.035, respectively), accompanied by a significant decrease in EBV reactivation (from 26% to 13%, p=0.033) and EBV-LPD (from 10.6% to 2.4%, p=0.029). The day-30 Vδ2+ T level remained an independent factor for EBV reactivation in patients with different MMF durations (p=0.007). In the in-vitro experiments, MMF inhibited Vδ2+ T-cell expansion and its cytotoxicity on EBV-transformed malignant cells. Furthermore, the therapeutic and prophylactic effects of adoptively transferred human Vδ2+ T cells were attenuated by the MMF treatment in immunodeficient mice with EBV-LPD.Conclusions These results elucidated a negative effect of immunosuppressants on the anti-EBV capacity of Vδ2+ T cells. Strategies that appropriately relieve the immunosuppression may improve anti-EBV immunity by increasing the activity of Vδ2+ T cells after alloHCT.